A water-based environmentally friendly high-strength waterproof adhesive and preparation method thereof

By preparing the sixth ring oxygen -like MOSS modified lignin and soybean -separated protein reactions, the problem of poor water resistance and low glue strength of adhesives and water -resistant water -resistant water -resistant adhesives And the wide range of advantages.

CN118308065BActive Publication Date: 2025-01-28深圳市道丰宁科技有限公司
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410665585.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-27
Publication Date
2025-01-28
Estimated Expiration
2044-05-27

AI Technical Summary

Technical Problem

The existing adhesives have poor water resistance and low strength during use, and the traditional epoxy crosslinking agents have poor compatibility with water-based soy protein adhesives, resulting in large fluctuations in the adhesive strength.

Method used

By preparing the sixth ring oxygen -shaped MOSS hybrid materials and amino -library quality reactions to synthesize the sixth ring oxygen -like MOSS modified lignin, and separate it from soybean protein reactions to form water -based and environmentally friendly high -intensity waterproof adhesives.

Benefits of technology

The shear strength and tensile strength of the adhesive have been improved, the intensity and water resistance of the glue is enhanced, and the water resistance of soy protein adhesives is low and the intensity strength is low. At the same time, it has the advantages of green environmental protection and a wide range of applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_4
    Figure SMS_4
  • Figure SMS_5
    Figure SMS_5
Patent Text Reader

Abstract

The invention relates to the technical field of adhesives, and discloses a water-based, environment-friendly, high-strength waterproof adhesive and a preparation method thereof. Hexaepoxy cyclic MOSS modified lignin is an organic-inorganic nano hybrid molecule with a three-dimensional cyclic special structure, a main chain of which is a ring composed of Si-O-Si bonds, and a benzene ring with a rigid structure is provided on the side chain of the ring, and the mechanical properties are relatively excellent; the polyepoxy groups in the structure can react chemically with carbonyl groups and amino groups in soybean protein molecules to form a stable interpenetrating network structure, thereby inhibiting water molecules from entering the interior of the adhesive, overcoming the problem that the soybean protein adhesive is prone to foaming and debonding when encountering water, and having excellent high temperature resistance, water resistance and waterproof properties; aminated lignin is a natural degradable macromolecule with a three-dimensional structure, contains a certain amount of active groups such as hydroxyl groups, carboxyl groups, amino groups, etc., can improve the water resistance and bonding strength of the soybean protein adhesive, is green and environmentally friendly, and has strong feasibility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adhesives, and in particular to a water-based, environment-friendly, high-strength waterproof adhesive and a preparation method thereof. Background Art

[0002] As a polymer substance with excellent bonding properties, adhesives have been widely used in people's production and life since ancient times. At present, the adhesives used by my country's wood and wood-based panel companies are mainly derived from non-renewable resources such as petroleum-based, such as urea-formaldehyde resin adhesives, phenol-formaldehyde resin adhesives, etc. During the production and use process, aldehyde adhesives will continuously release harmful gases such as free formaldehyde to the outside world, affecting air quality and endangering human health. In addition, the use of these adhesives will consume a large amount of petroleum resources and accelerate the depletion and shortage of resources. With the continuous improvement of people's requirements for living environment, the green production and application of adhesives has become an inevitable trend. Therefore, the use of abundant and renewable biomass resources to develop formaldehyde-free and environmentally friendly adhesives has gradually become the focus of people's attention.

[0003] Soy protein adhesive, an important component of biomass adhesives, has the advantages of a wide range of raw material sources, being renewable, and being green and environmentally friendly. It can be used in the production of single-board artificial board products such as plywood and blockboard. However, soy protein isolate has a large molecular weight, a complex structure, and poor water resistance. At the same time, soy protein isolate is prone to aging and brittleness under environmental conditions and has low strength. In practical applications, it is easy to affect the service life and quality stability of the board, limiting its wide application in high-performance wood composite materials. Currently, most of the modified soy protein adhesives use organic solvent-based epoxy crosslinking agents, but the epoxy crosslinking agent has poor compatibility with water-based soy protein adhesives, which can easily cause uneven dispersion of the crosslinking agent in the adhesive, resulting in large fluctuations in the bonding strength of the prepared artificial board and low effective utilization of the crosslinking agent.

[0004] Chinese patent CN113801616B discloses a modified lignin weather-resistant adhesive, which is obtained by phenolizing acidic lignin with components such as resorcinol, acetone, and concentrated sulfuric acid to obtain phenolized lignin. The adhesive prepared by using the phenolized lignin containing more phenolic hydroxyl groups and free reaction sites has excellent heat resistance and flame retardancy, good adhesion and is not easy to fall off. However, the adhesive contains phenolic resin, which releases harmful formaldehyde gas during use, which does not meet the requirements of green environmental protection. Therefore, a simple, green, and low-cost method is sought to compound lignin with plant protein to prepare high-performance green adhesive, which has great industrial prospects. The present invention prepares epoxy MOSS monomers with excellent mechanical properties, reacts with lignin to synthesize lignin epoxy grafts, and uses them as cross-linking agents to modify soybean protein adhesives to solve the problems of poor water resistance and low bonding strength of soybean protein adhesives. It is green and environmentally friendly and has strong feasibility. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the prior art, provide a water-based, environmentally friendly, high-strength waterproof adhesive and a preparation method thereof, and solve the problems of poor water resistance and low strength of the prior adhesive.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is:

[0007] A method for preparing a water-based, environmentally friendly, high-strength waterproof adhesive comprises the following steps:

[0008] (1) Add aminated lignin and a sodium hydroxide aqueous solution with a mass fraction of 1-2.5% into a reaction flask, stir evenly, add the hexaepoxy cyclic MOSS hybrid material, stir to react, and after the reaction is completed, perform vacuum distillation, wash with deionized water, and freeze-dry to obtain the hexaepoxy cyclic MOSS modified lignin.

[0009] (2) Add 100 g of soy protein isolate, 15-20 g of sodium hydroxide and 30-45 g of deionized water into a reaction flask, stir evenly, react at 75-90 ° C for 80-120 min, cool to 40-50 ° C, adjust the pH to 9.0-9.5 with citric acid, add 3-15 g of hexaepoxy cyclic MOSS modified lignin, and continue to react at 75-90 ° C for 30-50 min to obtain a water-based, environmentally friendly, high-strength waterproof adhesive.

[0010] Furthermore, in step (1), the ratio of the aminated lignin, the sodium hydroxide aqueous solution, and the hexaepoxy cyclic MOSS hybrid material is 1 g: (10-15) mL: (2-3.5) g.

[0011] Furthermore, in step (1), the reaction temperature is 35-50°C and the reaction time is 2-3h.

[0012] Furthermore, in step (2), the sodium hydroxide is a sodium hydroxide solution with a mass fraction of 15-30%.

[0013] Furthermore, the method for preparing the hexaepoxy cyclic MOSS hybrid material in step (1) comprises the following steps:

[0014] Step S1, under nitrogen atmosphere, add toluene, pyridine and dimethyl monochlorosilane to a reaction flask, stir evenly, add hexaphenylcyclohexasilane nickel-sodium salt, react at 20-35° C. for 16-32 hours, filter, distill the filtrate under reduced pressure, wash with deionized water until neutral, and dry to obtain a hexaphenylsilane hydrogen ring MOSS hybrid material with the structural formula: .

[0015] Step S2: under nitrogen atmosphere, add hexaphenylsilane MOSS hybrid material and toluene to a reaction flask, stir evenly, add allyl glycidyl ether and chloroplatinic acid, stir to react, and after the reaction is completed, perform vacuum distillation to obtain hexaepoxy ring MOSS hybrid material. The preparation reaction formula is:

[0016]

[0017] Furthermore, in step S1, the ratio of toluene, pyridine, dimethyl monochlorosilane, and hexaphenylcyclohexasilane nickel-sodium salt is (20-30) mL: (4.2-5.2) g: (0.9-1.3) g: 1 g.

[0018] Furthermore, the preparation method of hexaphenylcyclohexasilane nickel-sodium salt in step S1 includes the following steps: under a nitrogen atmosphere, adding 1g of phenyltrimethoxysilane, 0.2-0.3g of sodium hydroxide, 0.1-0.5mL of deionized water and 15-25mL of n-butanol to a reaction flask, stirring evenly, reacting at 120-130°C for 1-2h, adding 0.4-0.6g of dichlorohexaamminenickel, continuing the reaction for 2-4h, filtering while hot, distilling under reduced pressure, cooling to precipitate, filtering to obtain hexaphenylcyclohexasilane nickel-sodium salt.

[0019] Furthermore, in step S2, the ratio of the hexaphenylsilane MOSS hybrid material, toluene, allyl glycidyl ether, and chloroplatinic acid is 1 g: (5-10) mL: (1.1-1.5) g: (0.03-0.05) g.

[0020] Furthermore, in step S2, the reaction temperature is 80-95° C., and the reaction time is 12-24 h.

[0021] Furthermore, water-based, environmentally friendly, high-strength waterproof adhesives are used in the plywood field.

[0022] By adopting the above technical solution, the beneficial effects of the present invention are:

[0023] The invention firstly reacts dimethyl monochlorosilane and hexaphenylcyclohexasilanol nickel-sodium salt to obtain a hexaphenylsilyl hydrogen cyclo MOSS hybrid material, then reacts with allyl glycidyl ether under the catalysis of chloroplatinic acid to undergo silylation to obtain a hexaepoxy cyclic MOSS hybrid material, then utilizes the epoxy groups on the surface of the hybrid material to graft with aminated lignin to obtain a hexaepoxy cyclic MOSS modified lignin, and finally reacts with soy protein isolate to obtain a water-based, environmentally friendly, high-strength waterproof adhesive.

[0024] Hexaepoxy cyclic MOSS modified lignin itself is an organic-inorganic nano-hybrid molecule with a special three-dimensional ring structure. Its main chain is a ring composed of Si-O-Si bonds, and there are rigid benzene rings on the side chains of the rings, with excellent mechanical properties. The multiple epoxy groups in its structure can be used as three-dimensional chemical cross-linking sites, reacting with soy protein isolate molecular groups in a cross-linking manner to form a three-dimensional cross-linked network structure, which enhances the shear strength and tensile strength of the adhesive and greatly reduces the cohesive failure of the adhesive, thereby improving its bonding strength and water resistance.

[0025] The epoxy groups of the hexaepoxy cyclic MOSS modified lignin react chemically with the carbonyl and amino groups in the soy protein isolate molecules to form a stable interpenetrating network structure, which inhibits water molecules from entering the adhesive. The Si-O-Si has a strong bond force and a large bond energy, and can withstand high temperatures, thereby overcoming the problem that the soy protein adhesive is prone to foaming and debonding when it comes into contact with water, so that the prepared adhesive has excellent high temperature resistance and water and waterproof properties. The aminated lignin is a natural macromolecule with a three-dimensional structure, which contains a certain amount of active groups such as hydroxyl, carboxyl, and amino groups. The aminated lignin and the soy protein isolate are both biodegradable materials. The macroadhesive prepared by the present invention has relatively excellent water resistance and bonding strength, and also has the advantages of being green, environmentally friendly, and having a wide range of applications. DETAILED DESCRIPTION

[0026] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Preparation of aminated lignin: Under a nitrogen atmosphere, 11.0 g of lignin and 1.06 g of ferrous chloride were added to 110 mL of deionized water, stirred for 20 min, and then 10 mL of hydrogen peroxide was added dropwise, and the mixture was reacted at 40 ° C for 5 h. The product was filtered, washed, and freeze-dried to obtain oxidized lignin. Then, 5.68 g of oxidized lignin was evenly stirred with 11.2 mL of ammonia water and 160 mL of methanol, and 2.5 g of sodium borohydride was added. The mixture was reacted at 60 ° C for 2 h, distilled under reduced pressure, washed with deionized water, and dried to obtain aminated lignin.

[0028] Preparation of dichlorohexaamminenickel: Add 43 g of nickel chloride hexahydrate and 100 mL of deionized water into a beaker, stir to dissolve, then add 400 mL of ammonia water, continue stirring for 30 min, seal the beaker with a sealing film and put it in a freezer, crystallize at -4°C, filter, wash with ethanol, and dry to obtain dichlorohexaamminenickel.

[0029] Example 1

[0030] (1) Under nitrogen atmosphere, add 12 g of phenyltrimethoxysilane, 3 g of sodium hydroxide, 3.5 mL of deionized water and 240 mL of n-butanol into a reaction flask, stir evenly, react at 125°C for 1.5 h, add 6 g of dichlorohexaamminenickel, continue to react for 3 h, filter while hot, distill under reduced pressure, cool to precipitate, and filter to obtain hexaphenylcyclohexasilane nickel-sodium salt.

[0031] (2) Under nitrogen atmosphere, add 20 mL of toluene, 37 g of pyridine and 8.8 g of dimethyl monochlorosilane into the reaction flask, stir evenly, add 8 g of hexaphenylcyclohexasilane nickel-sodium salt, react at 25 °C for 24 h, filter, distill the filtrate under reduced pressure, wash with deionized water until neutral, and dry to obtain the hexaphenylsilane hydrogen ring MOSS hybrid material.

[0032] (3) Under nitrogen atmosphere, 5 g of hexaphenylsilane MOSS hybrid material and 30 mL of toluene were added to the reaction flask. After stirring evenly, 6.5 g of allyl glycidyl ether and 0.2 g of chloroplatinic acid were added. The mixture was reacted at 85 °C for 16 h and then distilled under reduced pressure to obtain the hexaepoxy MOSS hybrid material.

[0033] (4) Add 2 g of aminated lignin and 25 mL of 2% sodium hydroxide aqueous solution into a reaction flask, stir evenly, then add 6 g of hexacyclic MOSS hybrid material, react at 45 °C for 2.5 h, distill under reduced pressure, wash with deionized water, and freeze-dry to obtain hexacyclic MOSS modified lignin.

[0034] (5) 100 g of soy protein isolate, 15 g of 25% sodium hydroxide solution and 35 g of deionized water were added to the reaction flask, stirred evenly, reacted at 80 °C for 90 min, cooled to 45 °C, adjusted the pH to 9.2 with citric acid, added 3 g of hexaepoxy cyclic MOSS modified lignin, and continued to react at 80 °C for 40 min to obtain a water-based, environmentally friendly, high-strength waterproof adhesive.

[0035] Example 2

[0036] (1) Under nitrogen atmosphere, add 20 g of phenyltrimethoxysilane, 4 g of sodium hydroxide, 2 mL of deionized water and 300 mL of n-butanol into a reaction flask, stir evenly, react at 130 °C for 1 h, add 8 g of dichlorohexaamminenickel, continue to react for 4 h, filter while hot, distill under reduced pressure, cool to precipitate, and filter to obtain hexaphenylcyclohexasilane nickel-sodium salt.

[0037] (2) Under nitrogen atmosphere, 320 mL of toluene, 72 g of pyridine and 14.4 g of dimethyl monochlorosilane were added to the reaction flask. After stirring evenly, 16 g of hexaphenylcyclohexasilane nickel-sodium salt was added. The mixture was reacted at 35 °C for 16 h. The filtrate was filtered and distilled under reduced pressure. The filtrate was washed with deionized water until neutral and dried to obtain the hexaphenylsilane hydrogen ring MOSS hybrid material.

[0038] (3) Under nitrogen atmosphere, 10 g of hexaphenylsilane MOSS hybrid material and 50 mL of toluene were added to the reaction flask. After stirring evenly, 11 g of allyl glycidyl ether and 0.3 g of chloroplatinic acid were added. The mixture was reacted at 95 °C for 12 h and then distilled under reduced pressure to obtain the hexaepoxy MOSS hybrid material.

[0039] (4) Add 8 g of aminated lignin and 80 mL of 2.5% sodium hydroxide aqueous solution into a reaction flask, stir evenly, add 16 g of hexaepoxy cyclic MOSS hybrid material, react at 50 °C for 2 h, distill under reduced pressure, wash with deionized water, and freeze-dry to obtain hexaepoxy cyclic MOSS modified lignin.

[0040] (5) 100 g of soy protein isolate, 20 g of 15% sodium hydroxide solution and 30 g of deionized water were added to the reaction flask, stirred evenly, reacted at 90 °C for 80 min, cooled to 50 °C, adjusted the pH to 9.5 with citric acid, added 6 g of hexaepoxy cyclic MOSS modified lignin, and continued to react at 90 °C for 30 min to obtain a water-based, environmentally friendly, high-strength waterproof adhesive.

[0041] Example 3

[0042] (1) Under nitrogen atmosphere, add 10 g of phenyltrimethoxysilane, 3 g of sodium hydroxide, 5 mL of deionized water and 250 mL of n-butanol into a reaction flask, stir evenly, react at 120 °C for 2 h, add 6 g of dichlorohexaamminenickel, continue to react for 4 h, filter while hot, distill under reduced pressure, cool to precipitate, and filter to obtain hexaphenylcyclohexasilane nickel-sodium salt.

[0043] (2) Under nitrogen atmosphere, 150 mL of toluene, 26 g of pyridine and 6.5 g of dimethyl monochlorosilane were added to the reaction flask. After stirring evenly, 5 g of hexaphenylcyclohexasilane nickel-sodium salt was added. The mixture was reacted at 20 °C for 32 h. The filtrate was filtered and distilled under reduced pressure. The filtrate was washed with deionized water until neutral and dried to obtain the hexaphenylsilane hydrogen ring MOSS hybrid material.

[0044] (3) Under nitrogen atmosphere, 10 g of hexaphenylsilane MOSS hybrid material and 100 mL of toluene were added to the reaction flask. After stirring evenly, 15 g of allyl glycidyl ether and 0.5 g of chloroplatinic acid were added. The mixture was reacted at 80 °C for 24 h and distilled under reduced pressure to obtain the hexacyclic MOSS hybrid material.

[0045] (4) Add 5 g of aminated lignin and 75 mL of 1% sodium hydroxide aqueous solution into a reaction flask, stir evenly, then add 17.5 g of hexaepoxy cyclic MOSS hybrid material, react at 35 °C for 3 h, distill under reduced pressure, wash with deionized water, and freeze-dry to obtain hexaepoxy cyclic MOSS modified lignin.

[0046] (5) 100 g of soy protein isolate, 20 g of 15% sodium hydroxide solution and 45 g of deionized water were added to a reaction flask, stirred evenly, reacted at 75 °C for 120 min, cooled to 40 °C, adjusted the pH to 9.0 with citric acid, added 9 g of hexaepoxy cyclic MOSS modified lignin, and continued to react at 75 °C for 30 min to obtain a water-based, environmentally friendly, high-strength waterproof adhesive.

[0047] Example 4

[0048] (1) Under nitrogen atmosphere, add 30 g of phenyltrimethoxysilane, 6.6 g of sodium hydroxide, 10.5 mL of deionized water and 540 mL of n-butanol into a reaction flask, stir evenly, react at 120 °C for 2 h, add 15.6 g of dichlorohexaamminenickel, continue to react for 3.5 h, filter while hot, distill under reduced pressure, cool to precipitate, and filter to obtain hexaphenylcyclohexasilane nickel-sodium salt.

[0049] (2) Under nitrogen atmosphere, 550 mL of toluene, 120 g of pyridine and 25 g of dimethyl monochlorosilane were added to the reaction flask. After stirring evenly, 25 g of hexaphenylcyclohexasilane nickel-sodium salt was added. The mixture was reacted at 30 °C for 18 h. The filtrate was filtered and distilled under reduced pressure. The filtrate was washed with deionized water until neutral and dried to obtain the hexaphenylsilane hydrogen ring MOSS hybrid material.

[0050] (3) Under nitrogen atmosphere, 18 g of hexaphenylsilane MOSS hybrid material and 95 mL of toluene were added to the reaction flask. After stirring evenly, 24.3 g of allyl glycidyl ether and 0.72 g of chloroplatinic acid were added. The mixture was reacted at 90 °C for 16 h and distilled under reduced pressure to obtain a hexacyclic MOSS hybrid material.

[0051] (4) Add 12 g of aminated lignin and 160 mL of 2% sodium hydroxide aqueous solution into a reaction flask, stir evenly, then add 30 g of hexacyclic MOSS hybrid material, react at 50 °C for 2.5 h, distill under reduced pressure, wash with deionized water, and freeze-dry to obtain hexacyclic MOSS modified lignin.

[0052] (5) 100 g of soy protein isolate, 20 g of 20% sodium hydroxide solution and 40 g of deionized water were added to the reaction flask, stirred evenly, reacted at 85 °C for 110 min, cooled to 45 °C, adjusted the pH to 9.3 with citric acid, added 12 g of hexaepoxy cyclic MOSS modified lignin, and continued to react at 85 °C for 35 min to obtain a water-based, environmentally friendly, high-strength waterproof adhesive.

[0053] Example 5

[0054] (1) Under nitrogen atmosphere, add 8.5 g of phenyltrimethoxysilane, 2.21 g of sodium hydroxide, 2.6 mL of deionized water and 155 mL of n-butanol into a reaction flask, stir evenly, react at 130 °C for 2 h, add 3.9 g of dichlorohexaamminenickel, continue to react for 3 h, filter while hot, distill under reduced pressure, cool to precipitate, and filter to obtain hexaphenylcyclohexasilane nickel-sodium salt.

[0055] (2) Under nitrogen atmosphere, 140 mL of toluene, 31.2 g of pyridine and 7.8 g of dimethyl monochlorosilane were added to the reaction flask. After stirring evenly, 6.5 g of hexaphenylcyclohexasilane nickel-sodium salt was added. The mixture was reacted at 30 °C for 24 h. The filtrate was filtered and distilled under reduced pressure. The filtrate was washed with deionized water until neutral and dried to obtain the hexaphenylsilane hydrogen ring MOSS hybrid material.

[0056] (3) Under nitrogen atmosphere, 4 g of hexaphenylsilane MOSS hybrid material and 30 mL of toluene were added to the reaction flask. After stirring evenly, 5 g of allyl glycidyl ether and 0.14 g of chloroplatinic acid were added. The mixture was reacted at 90 °C for 15 h and then distilled under reduced pressure to obtain the hexaepoxy MOSS hybrid material.

[0057] (4) Add 2.5 g of aminated lignin and 30 mL of 2% sodium hydroxide aqueous solution into a reaction flask, stir evenly, then add 7 g of hexacyclic MOSS hybrid material, react at 45 °C for 3 h, distill under reduced pressure, wash with deionized water, and freeze-dry to obtain hexacyclic MOSS modified lignin.

[0058] (5) Add 100 g of soy protein isolate, 18 g of 30% sodium hydroxide solution and 40 g of deionized water into a reaction flask, stir evenly, react at 80 °C for 100 min, cool to 50 °C, adjust the pH to 9.0 with citric acid, add 15 g of hexaepoxy cyclic MOSS modified lignin, and continue to react at 80 °C for 40 min to obtain a water-based, environmentally friendly, high-strength waterproof adhesive.

[0059] Comparative Example 1

[0060] Add 100g of soy protein isolate, 15g of 25% sodium hydroxide solution and 35g of deionized water to the reaction flask, stir evenly, react at 80°C for 90min, cool to 45°C, adjust pH to 9.2 with citric acid, add 3g of trimethylolpropane triglycidyl ether (structural formula: ), and continue the reaction at 80°C for 40 min to obtain a waterproof adhesive.

[0061] Comparative Example 2

[0062] 100 g of soy protein isolate, 15 g of 25% sodium hydroxide solution and 35 g of deionized water were added to a reaction flask, stirred evenly, reacted at 80° C. for 90 min, cooled to 45° C., and the pH was adjusted to 9.2 with citric acid to obtain an adhesive.

[0063] Preparation of plywood: Poplar veneers with specifications of 300×300×2mm and modified soy protein adhesive were selected as raw materials, and three layers of plywood were pressed. The veneers were coated with double-sided glue, and the poplar veneers after glue coating were assembled perpendicular to each other according to the grain direction. The double-sided glue coating amount was 350g / m 2 After being placed at room temperature for 10-20 minutes, it was placed in a cold press with a pressure of 0.85MPa for pre-pressing for 10 minutes, and then hot-pressed in a hot press with a temperature of 120℃ and a pressure of 0.9MPa for 6 minutes. The pressed plywood was placed at room temperature for 24 hours before performance testing.

[0064] According to the relevant standards in GB / T 17657-2013 "Test methods for physical and chemical properties of wood-based panels and veneer wood-based panels", the dry bonding strength of plywood prepared with adhesive was determined. The prepared plywood was then immersed in 65°C hot water for 48 hours. After being taken out, its water-resistant bonding strength was tested. The experiment was repeated three times and the average value was taken.

[0065] Table 1 Strength and water resistance test

[0066]

[0067] It can be seen from the test results in the above table that with the increase of the content of hexacyclic MOSS modified lignin, the dry glue bonding strength of the plywood gradually increases, and the dry glue bonding strength in Example 4 reaches 2.23MPa. This is because the hexacyclic MOSS modified lignin itself is an organic-inorganic nano-hybrid molecule with a three-dimensional cyclic special structure. Its main chain is a ring composed of Si-O-Si bonds, and there are benzene rings with a rigid structure on the side chains of the ring. Its mechanical properties are relatively excellent, and it can form a cross-linked structure through physical or chemical interactions, which greatly reduces the cohesive destructive effect of the adhesive, thereby improving its bonding strength; at the same time, after the plywood is soaked in hot water, its water-resistant bonding strength is not much different from the dry glue bonding strength. This is because the hexacyclic MOSS modified lignin contains multiple epoxy groups, which can be used as a cross-linking agent to cross-link with the soy protein isolate molecular group to form a three-dimensional cross-linked network structure, thereby improving its water resistance.

[0068] Comparative Example 1 contains trimethylolpropane triglycidyl ether, which does not have a MOSS organic-inorganic hybrid system, and the strength of its adhesive is not good. However, it contains epoxy groups, which can be cross-linked with soy protein isolate to form a cross-linked network structure. Therefore, after being soaked in hot water, the water-resistant bonding strength is 1.10 MPa, which is not much different from the dry bonding strength. Comparative Example 2 contains pure soy protein adhesive, which is mainly affected by hydrogen bonds between molecules and is easily invaded by water molecules, so that its water-resistant bonding strength is significantly reduced and it has no waterproof effect.

[0069] Test of moisture and heat aging resistance: The prepared plywood was treated in a constant temperature and humidity chamber at a temperature of 120°C and a relative humidity of 95% for 48 hours, and its bonding strength was tested, and the presence of blistering, debonding and other cracking phenomena was observed.

[0070] Table 2 Test of moisture and heat aging resistance

[0071]

[0072] It can be seen from the test results in the above table that with the increase of the content of epoxy cyclic MOSS modified lignin, the moisture and heat aging resistance of the plywood is gradually enhanced. The bonding strength in Example 4 reaches 1.92MPa, which meets the requirements of Class II plywood specified in the national standard GB / T 9846-2015, indicating that the degree of cross-linking of the adhesive modified by the MOSS hybrid material is significantly improved. After being treated in an environment with a temperature of 120°C and a humidity of 95% for 48 hours, the plywood made of the adhesive still does not bubble or debond, and has good moisture and heat aging resistance.

[0073] Preparation of adhesive film: The prepared adhesive was applied to a polytetrafluoroethylene plate using a film applicator to prepare an adhesive film with a thickness of 500 μm, and dried and cured at 50°C for 12 h; the tensile properties were tested in accordance with GB / T 1040.1-2006; the shear strength was tested in accordance with GB / T5849-2006.

[0074] Table 3 Mechanical properties test

[0075]

[0076] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a water-based, environmentally friendly, high-strength waterproof adhesive, characterized in that: The preparation method comprises the following steps: (1) Add aminated lignin and a sodium hydroxide aqueous solution with a mass fraction of 1-2.5% into a reaction flask, stir evenly, add hexaepoxy cyclic MOSS hybrid material, stir to react, and after the reaction is completed, perform vacuum distillation, wash with deionized water, and freeze-dry to obtain hexaepoxy cyclic MOSS modified lignin; (2) Add 100 g of soy protein isolate, 15-20 g of sodium hydroxide and 30-45 g of deionized water to a reaction flask, stir evenly, react at 75-90° C. for 80-120 min, cool to 40-50° C., adjust the pH to 9.0-9.5 with citric acid, add 3-15 g of hexaepoxy cyclic MOSS modified lignin, and continue to react at 75-90° C. for 30-50 min to obtain a water-based, environmentally friendly, high-strength waterproof adhesive; The method for preparing the hexaepoxy cyclic MOSS hybrid material in step (1) comprises the following steps: Step S1, under a nitrogen atmosphere, add toluene, pyridine and dimethyl monochlorosilane into a reaction flask, stir evenly, add hexaphenylcyclohexasilane nickel-sodium salt, react at 20-35° C. for 16-32 hours, filter, distill the filtrate under reduced pressure, wash with deionized water until neutral, and dry to obtain a hexaphenylsilane hydrogen ring MOSS hybrid material; Step S2, under a nitrogen atmosphere, adding hexaphenylsilane MOSS hybrid material and toluene to a reaction flask, stirring evenly, adding allyl glycidyl ether and chloroplatinic acid, stirring for reaction, and after the reaction is completed, performing reduced pressure distillation to obtain a hexaepoxy cyclic MOSS hybrid material; In the step (1), the ratio of the aminated lignin, the sodium hydroxide aqueous solution, and the hexaepoxy cyclic MOSS hybrid material is 1 g: (10-15) mL: (2-3.5) g.

2. The method for preparing the water-based, environmentally friendly, high-strength waterproof adhesive according to claim 1, characterized in that: In the step (1), the reaction temperature is 35-50° C. and the reaction time is 2-3 h.

3. The method for preparing the water-based, environmentally friendly, high-strength waterproof adhesive according to claim 1, characterized in that: In the step (2), the sodium hydroxide is a sodium hydroxide solution with a mass fraction of 15-30%.

4. The method for preparing the water-based, environmentally friendly, high-strength waterproof adhesive according to claim 1, characterized in that: In the step S1, the ratio of toluene, pyridine, dimethyl monochlorosilane, and hexaphenylcyclohexasilane nickel-sodium salt is (20-30) mL: (4.2-5.2) g: (0.9-1.3) g: 1 g.

5. The method for preparing the water-based, environmentally friendly, high-strength waterproof adhesive according to claim 1, characterized in that: The preparation method of hexaphenylcyclohexasilane nickel-sodium salt in step S1 comprises the following steps: under a nitrogen atmosphere, adding 1 g of phenyltrimethoxysilane, 0.2-0.3 g of sodium hydroxide, 0.1-0.5 mL of deionized water and 15-25 mL of n-butanol into a reaction flask, stirring evenly, reacting at 120-130° C. for 1-2 h, adding 0.4-0.6 g of dichlorohexaamminenickel, continuing the reaction for 2-4 h, filtering while hot, distilling under reduced pressure, cooling to precipitate, filtering to obtain hexaphenylcyclohexasilane nickel-sodium salt.

6. The method for preparing the water-based, environmentally friendly, high-strength waterproof adhesive according to claim 1, characterized in that: In the step S2, the ratio of the hexaphenylsilane MOSS hybrid material, toluene, allyl glycidyl ether, and chloroplatinic acid is 1 g: (5-10) mL: (1.1-1.5) g: (0.03-0.05) g.

7. The method for preparing the water-based, environmentally friendly, high-strength waterproof adhesive according to claim 1, characterized in that: In step S2, the reaction temperature is 80-95° C. and the reaction time is 12-24 h.

8. Application of the water-based, environmentally friendly, high-strength waterproof adhesive obtained by the preparation method according to any one of claims 1 to 7 in the field of plywood.

Citation Information

Patent Citations

  • A modified lignin weather-resistant adhesive

    CN113801616B

  • Preparation method of novel epoxy group functionalized macrocyclic oligomeric silsesquioxane

    CN102584887A

  • Formaldehyde-free soybean protein powder adhesive, and preparation method and application thereof

    CN110835518A

  • Aminated lignin-soybean protein composite adhesive as well as preparation method and application thereof

    CN117343692A